Inferring school quality from rankings: the impact of school choice - Herresthal, C (University of Oxford, 2015)
School choice reforms allow families to apply to non-local schools and assign additional funding to schools based on families' demand. For these reforms to promote high-quality schools, families need to infer school quality from past performance, but past performance also depends on student ability. Because reforms alter the allocation of students to schools, it is unclear whether performance becomes more or less informative about quality. I model families as trading off estimated quality against proximity, and analyze a steady-state Bayesian-Nash equilibrium. I show that performance-based rankings become more informative about quality only if oversubscribed schools can choose whom to accept.